Faktor-Faktor yang Mempengaruhi Penggunaan E-Wallet di Batu Pahat - Safinah Amir Hamja; Alina Shamsuddin (Research in Management of Technology and Business, 2024)
An e-wallet is a digital wallet that enables customers to make online purchases using their mobile device. This enables users to do numerous transactions online at any time and from any location as long as they have access to their e-wallet account. The purpose of this research is to look at the elements that impact the adoption of e-wallets in the Batu Pahat community. This study also attempts to determine the link between the usefulness, ease of use, trustworthiness, and use of e-wallets in the Batu Pahat community. This study employs quantitative methodologies by distributing surveys. Based on the sample size, the questionnaire would be delivered to 382 respondents in Batu Pahat. The gathered data will next be quantitatively analysed using the Statistical Package for Social Science software. According to the findings of this survey, the degree of effect of E-wallet use is strong among the Batu Pahat population. Furthermore, the researchers discovered that usefulness, ease of use, and trustworthiness are elements that stimulate the adoption of E-wallets within the community. The researchers discovered that the variables of usefulness, ease of use, and trustworthiness had a favourable and substantial impact on the conclusions of this study.